Bluetooth revealed. - Miller, Brent A., ....-; Bisdikian, Chatschik, ....- (New Jersey : Prentice Hall, 2002)
Samenvatting:For users, the new Bluetooth wireless standard will cut through thecomplexity of wireless communications, enabling devices to communicateseamlessly. Bluetooth Revealed offers the first insider's view of theBluetooth standards: all the information and guidance professionals needto begin implementing Bluetooth solutions now.KEY TOPICS:After ahigh-level introduction to Bluetooth and the standards process, itreviews key design decisions driven by the use of the 2.4 GHz spectrum,power consumption restrictions, requirements for a global standard, andother key issues. It presents each key Bluetooth usage model, includingcordless computing, advanced headsets, file transfer/synchronization,dial-up networking, speakerphones and conference table applications,hidden computing, and more. Next, it reviews the entire specification inunprecedented depth: its purpose, scope, structure, andinterrelationships. The entire Bluetooth protocol stack is covered,including radio, baseband, and software layers; hardware and interfaces;and Link Manager and Logical Link Control and Adaptation Protocol(L2CAP). The book also contains detailed information on each majorBluetooth profile, showing how to achieve interoperable solutions for awide variety of applications. Finally, the authors preview Bluetooth'sfuture, including new automotive, imaging, printing, and otherapplications. MARKET:For every professional and wireless industryparticipant who needs to understand Bluetooth -- as implementers, fordeployment purposes, or to support management decision-making.
Keywords: Draadloze computernetwerken; Mobiele telefonie; Protocollen